Germanisms in the language of 19th – early 20th century folklore and dialect records - Pakhirka, Veranika U. (Journal of the Belarusian State University. Philology, 2023)
Germanisms recorded in the folklore and dialect records of the 19th – early 20th century are considered. Their thematic classification is given. The features of the graphical and orthographic transmission of the phonetic features of words of German origin, the specifics of their morphological and semantic assimilation by the Belarusian language are analysed. The derivational potential of Germanisms and their ability to form phraseological units are determined. Such characteristic features of Germanisms in the language of folklore and dialect records of the 19th – early 20th century become obvious, as a continuation of the old Belarusian traditions of borrowing assimilation, their further adaptation to the peculiarities of the Belarusian language of the period of formation of codified general literary norms.
Keywords: folklore and dialect records; lexical-thematic groups; phonetic adaptation; morphological adaptation; semantic adaptation; derivational potential; phrase-building activity